2011
DOI: 10.1136/aim.2010.003384
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Testing of Methods for Evaluation of Acupuncture for Emesis during Radiotherapy: A Randomised Single Subject Experimental Design

Abstract: Background Many acupuncture studies are of weak methodological quality, possibly due to lack of pilot testing. This pilot study tested design features, including test of feasibility, compliance to treatment and data collection, level of blinding success and the patients' potential perceived effects of the treatment, in preparation for an effi cacy study. Method A modifi ed single subject experimental design was conducted. 10 cancer patients were randomised to verum penetrating acupuncture or non-penetrating sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…The literature reviewed has shown that CTs could alleviate symptoms of chemotherapy, boost immunity and increase the QoL. [13363738] The use of CTs as a complement to conventional cancer treatment can be beneficial; however, adverse effects that could be harmful and interfere with oncological medical therapy should be considered. Thus, it is essential that the integration of conventional treatment and CTs for cancer should be properly managed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature reviewed has shown that CTs could alleviate symptoms of chemotherapy, boost immunity and increase the QoL. [13363738] The use of CTs as a complement to conventional cancer treatment can be beneficial; however, adverse effects that could be harmful and interfere with oncological medical therapy should be considered. Thus, it is essential that the integration of conventional treatment and CTs for cancer should be properly managed.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, herbal medicine, acupuncture, and yoga could alleviate the side effects of chemotherapy. [13363738] Thus, there is the need for further research regarding the efficacy and safety of CTs for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the study with 215 patients, a pilot study with 10 patients was conducted 24 . Verum and sham acupuncture was delivered close to (before or after) the first RT session for 30 minutes, 3 times per week for the first 2 weeks, then twice weekly for the remaining course of RT.…”
Section: Resultsmentioning
confidence: 99%
“…All studies have shown that acupuncture is associated with better outcome in relieving disorders than the control groups 20, 21, 22, 23, 24, 25, 29. This effect is observed in the verum acupuncture and in the sham acupuncture arms at least in 3 trials.…”
Section: Discussion and Future Trial Designmentioning
confidence: 95%
“…Literatürde akupunkturun kanserde ağrı, yorgunluk, anksiyete, depresyon, bulantı-kusma, ağız kuruluğu, gibi şikayetleri azaltmak, yaşam kalitesini artırmak için kullanılabileceği önerilmektedir. [57] Enblom, Tomasson, Hammar, Steineck ve Borjeson [58] radyoterapi alan hastalarda akapunkturun bulantıyı azalttığını bildirmişlerdir.…”
Section: Akupunkturunclassified